Implementasi Masase Neuroperfusi dan Alih Baring Terhadap Risiko Dekubitus Pasien Post Stroke - Erika Martining Wardani; Riezky Faisal Nugroho (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2022)
Decubitus is a problem in post-stroke patients that has yet to be resolved. The risk of pressure sores can be overcome with neuroperfusion massage therapy and bed rest. The purpose of this study was to determine the implementation of neuroperfusion massage and bed transfer on the risk of pressure sores in post-stroke patients. The design of this research is Quasy-Experiment with pre post test control group design. The population of all post-stroke patients treated at the Arosbaya Health Center in the Bangkalan Madura area was 30 people. A sample of 28 stroke patients was taken using a simple random sampling technique. The independent variable is neuroperfusion massage and bed transfer, the dependent variable is the risk of pressure sores. Data were analyzed using the Wilcoxon Signed Rank Test. The results showed that after the intervention of neuroperfusion massage (p value 0.000) and bed transfer (0.000) there was a reduction in the risk of pressure sores in post-stroke patients. Neuroperfusion massage and bed transfer are effective in preventing the risk of pressure ulcers in post-stroke patients. It is hoped that health workers can apply bed transfer therapy with neuroperfusion massage so that pressure sores can be handled optimally.